A Case of Allegoresis: A Buddhist Painter and His Patron in Mongolia - .Ts, Uranchimeg (Acta Mongolica, 2018)
The cosmopolitan Qing Empire (1644–1911), ruled by the ethnically non-Chinese Manchus, disintegrated in the early twentieth century ending China’s millennial dynastic history. One of the empire’s vassal states, Mongolia, once home to the largest Eurasian empire in history, seized the opportunity to proclaim its independence in the winter of 1911. Landlocked and sandwiched between China and Russia, Mongolia became a pawn in the political maneuverings of competing warlords, Communists (Bolsheviks), and Chinese Republicans.3At this time, an extraordinary painting was made for the Mongol ruler who was destined to be the last king of the Mongols before the Soviet takeover in 1921.